Evaluation of abdominal aortic calcification by plain CT predicts anastomotic leakage in laparoscopic surgery for colorectal cancer. (23rd December 2021) - Morita, Satoru; Tsuruta, Masashi; Okabayashi, Koji; Shigeta, Kohei; Seishima, Ryo; Monno, Masayoshi; Itano, Osamu; Kitagawa, Yuko
Abstract: Background: Anastomotic leakage is one of the most severe and critical complications of laparoscopic surgery for colorectal cancer. However, definitive preoperative predictors of anastomotic leakage remain elusive. With the ageing of society, the number of colorectal cancer patients with arteriosclerotic disease in Japan is increasing. This study was performed to evaluate the correlation between preoperative arteriosclerosis and anastomotic leakage. Methods: In total, 98 patients undergoing laparoscopic surgery for colorectal cancer with reconstruction using the double-stapling technique without diversion of the stoma were enrolled in the study. Preoperative assessment of arteriosclerotic disease was performed by abdominal computed tomography. The calcification volume percentage of the aorta between the level of the celiac artery root and aortic bifurcation was calculated using ZIOstation2 software, and the relationship between arteriosclerosis and anastomotic leakage was analysed. Results: Among 98 cases, anastomotic leakage was observed in 16 (16.3%). The median calcification volume percentage (range) was 2.35% (0–40.3%). Age, male sex, hypertension, dissection number, estimated glomerular filtration rate and tumour location were correlated with anastomotic leakage on statistical analysis. Statistical analysis showed that calcification volume percentage was one of the robust risk factors for anastomotic leakage (odds ratio: 1.09, 95% confidence interval: 1.03–1.17, P  < 0.01). Conclusions: Calcification of the abdominal aorta may be a promising predictor of AL after laparoscopic surgery for colorectal cancer reconstruction using the double-stapling technique. Abstract : Calcification of the abdominal aorta evaluated by the preoperative plain computed tomography indicates the risk of anastomotic leakage in laparoscopic surgery for colorectal cancer reconstruction using the double-stapling technique.